IMPROVEMENT OF FINANCIAL REPORTING ON ACCOUNTING FOR NON-CURRENT ASSETS (INNOVATIVE ECONOMY, 2026)
Zadorozhnyi M.Z. IMPROVEMENT OF FINANCIAL REPORTING ON ACCOUNTING FOR NON-CURRENT ASSETSPurpose. The aim of the article is to improve alternative forms of financial reporting in terms of presenting information on non-current assets in order to optimize the information support for different groups of stakeholders.Methodology of research. The study employs system analysis, logical generalization, comparative analysis, and a structural-functional approach, which made it possible to comprehensively reveal the prospects for improving alternative forms of financial reporting related to the accounting of non-current assets.Findings. The presentation of non-current assets in the financial reporting system of construction enterprises has been improved. The titles and codification of the relevant reporting items, as well as the structure and content of the sections of the Balance Sheet (Statement of Financial Position), the Statement of Financial Results (Statement of Comprehensive Income), the Cash Flow Statement (direct method), the Notes to the Annual Financial Statements have been clarified. The proposed changes are aimed at ensuring compliance with national and international regulations, achieving information synchronization with other elements of the accounting method, and establishing interrelations between different forms of financial reporting. Originality. For the first time, the use of the Notes to the Annual Financial Statements as an information base for the formation of internal (managerial) reporting in electronic form has been proposed. This is achieved through the refinement of the structure of the first, second, and third sections of the Notes, with the possibility of significant analytical detailing, as well as structural and dynamic interpretation of indicators. Such an approach enhances the informational value of reporting data on non-current assets for various groups of stakeholders.Practical value. The practical significance of the obtained results lies in the possibility of their application for improving the formation and presentation of information on non-current assets in the financial reporting of construction enterprises. The proposed approaches to clarifying the titles, codification, and content of reporting items can be applied in the preparation of the Balance Sheet (Statement of Financial Position), the Statement of Financial Results (Statement of Comprehensive Income), the Cash Flow Statement, the Notes to the Annual Financial Statements, and the Management Report.The research findings contribute to enhancing the informativeness and consistency of financial reporting, ensuring its compliance with national and international requirements, and strengthening the interrelation between individual reporting forms. The practical implementation of the proposed provisions will improve the quality of accounting and analytical information on non-current assets, which in turn will facilitate more well-grounded managerial decision-making and increase the transparency of construction enterprises for external users.Key words: financial reporting, accounting, non-current assets, reporting forms, Notes to the Annual Financial Statements, construction enterprises.
Keywords: financial reporting; accounting; non-current assets; reporting forms; Notes to the Annual Financial Statements; construction enterprises